Efektivitas Performance-Based Pay sebagai Instrumen Retensi Talenta di Industri Teknologi : Studi Kasus Penggunaan Insentif Berbasis Saham pada Alphabet Inc. (Google) - Halimatus Sa’diah; Agung Zulfikri (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effectiveness of performance-based pay (PBP) in the form of stock-based incentives as a talent retention instrument in the technology industry, with a case study of Alphabet Inc. (Google). This research employs a qualitative approach using a case study method to gain an in-depth understanding of the mechanisms, effectiveness, and limitations of stock-based compensation systems. The data were collected through document analysis and literature review, including company annual reports and relevant academic journals. Data analysis was conducted using an interactive model, involving data reduction and descriptive data display. The findings indicate that the implementation of stock-based PBP through Restricted Stock Units (RSU) at Alphabet Inc. serves as an effective retention mechanism, particularly through a vesting system that creates medium-term financial attachment among employees. This system enhances motivation, loyalty, and employees’ intention to stay, especially among high-performing talents. However, its effectiveness is relative, as it is influenced by external factors such as stock price volatility, as well as internal factors including perceived fairness and compensation transparency. In addition, work pressure and evolving workforce preferences pose challenges to the sustainability of this system. Therefore, stock-based PBP cannot function as a standalone retention strategy and should be integrated with non-financial factors such as work environment and career development.